International Control of Price Levels - Reed, Harold L. (Quarterly Journal of Economics, 1931)
Journal Article International Control of Price Levels Get access Harold L. Reed Harold L. Reed Cornell University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 45, Issue 2, February 1931, Pages 357–364, https://doi.org/10.2307/1885480 Published: 01 February 1931